An examination of hepatotoxicity and nephrotoxicity of a new antiadhesive preparation (experimental study) - I. A. Shurygina; N. I. Ayushinova; L. V. Rodionova; E. E. Chepurnykh; M. G. Shurygin (Acta Biomedica Scientifica, 2017)
Adhesive process in the abdominal cavity was simulated in Wistar rats. The animals were divided into two groups: the main one - simulation of adhesive process in the abdominal cavity and introduction of 3 ml of saline into the abdominal cavity; and the controls - simulation of adhesive process in the abdominal cavity and introduction of 3 ml of new antiadhesive preparation. We evaluated biochemical parameters at eight time points during the period from 2 hours to 28 days. The introduced drug for adhesion prevention did not affect the protein-synthetic function of the liver: the blood level of whole protein was the same in both groups and remained within the normal range throughout the follow-up period. The blood level of creatinine, which is the end product of protein metabolism reflecting the renal excretory function, was within normal values in both groups throughout the observation period. Significant differences between the groups were noted only on the 28th day of the experiment: in the main group creatinine level was higher as compared to the control group (p = 0.014), but remained within the normal range. The same pattern was observed when evaluating the blood urea level, which reflects the renal excretory function - the blood urea level remained normal in both groups throughout the experiment. Hence, the new antiadhesive drug does not produce toxic effect on liver and kidneys in a single intraperitoneal introduction in experiment. Biochemical indices are the same as in single intraperitoneal infusion of saline.